Evaluation of the Baermann–Wetzel method for detecting lungworm larvae in wild ruminants from faecal samples. (8th March 2021) - Carrau, T.; Martínez-Carrasco, C.; Garijo, M.M.; Alonso, F.; Ruiz de Ybáñez, R.; Tizzani, P.
Abstract: Lungworms can exert a negative impact on wild ruminant fitness; for this reason, the diagnosis of the associated diseases is an important prevention measure. The Baerman–Wetzel technique is the most usual method for the diagnosis of bronchopulmonary nematodes and is based on the active migration and movement of their first-stage larvae. Pulmonary tissue samples are frequently used for the post-mortem diagnosis of these parasites, but this kind of sample is not always available and easy to obtain. Faecal samples represent a more accessible choice for parasite monitoring. This work aimed to evaluate the agreement between the results obtained by the Baermann–Wetzel technique when samples of lung parenchyma or faeces from wild ruminants are used. A good level of agreement as well as a similar sensitivity between the two types of sample were observed, validating the use of faecal samples as a less invasive and cost-effective alternative for the monitoring of lungworm in wild ruminant populations.